Robust control for incremental quadratic constrained nonlinear time-delay systems subject to actuator saturation - Huang, Jun; Yang, Lin; Trinh, Hieu (Applied mathematics and computation, 2021)
•This paper propose the IQC nonlinear function with time delay for the first time and the nonlinear term is dealt with by the S-procedure.•The saturated feedback law is constructed and the considered systems are proved to be exponentially stable under the given conditions.•An optimization problem of maximizing the estimation of DA is derived by CHLF approach, and two simulations are provided to show that the proposed method can provide a larger estimation of DA than the QLF method. This article presents a saturation controller design method for a type of nonlinear time-delay systems. Different from the current works, the nonlinear systems considered herein satisfy an incremental quadratic constraint, which is a more general nonlinearity. Firstly, for the constraint in the actuator, the convex set theory is employed to transform the saturated feedback law into a parameterized linear convex hull set. Next, the convex hull Lyapunov function is constructed to obtain sufficient conditions for exponential stability of the closed-loop system. In addition, by solving an optimization problem, the maximal estimation of domain of attraction is also determined. Finally, numerical examples are provided to verify the proposed method.